Death is Nothing at All. Heirs, their Absence and Lineage Strategies in Traditional China - Kentaro Matsubara (L'Atelier du CRH)
The term “inheritance” may not be best suited to describe the traditional Chinese system for transmitting property rights through generations. What was absent was the notion that property was owned by an individual who could unequivocally decide how to use or dispose of the same property. This absence was part and parcel with a system where property (which was nominally held by the household and could be disposed of as the household head) was seen to ultimately belong to the continuity of the male line (zong), and would be transferred through generations in manners not necessarily related to the death (or survival) of the current household head. Through a reconstruction of this system and a description of various strategies, including ancestral property and posthumous marriages, this chapter explains how a very different view of life and death led to the development of a very different system regarding the treatment of property in the absence of living, unequivocally recognised owners.